La masía : un Miró para Mrs. Hemingway - Fernández de Castro, Alex, 1966- (Biblioteca Javier Coy d'estudis nord-americans ;, 2015)
About the painting La masía by Joan Miró (1893-1983), owned by Ernest Hemingway (1899-1961).